N-doped carbon xerogels as adsorbents for the removal of heavy metal ions from aqueous solution1. Issue 10 (6th February 2015) - Yang, Bin; Yu, Chengxiang; Yu, Qingni; Zhang, Xingwang; Li, Zhongjian; Lei, Lecheng
<x xml:space="preserve">Abstract</x> The adsorption capacity for Pb, Zn and Cu ions in aqueous solution can be significantly improved by the introduction of N into the carbon xerogel (CX) matrix in the basis of the extraordinary textural property.